THE ROLE OF READING ARTICLES TO IMPROVE ENGLISH LEARNERS’ READING SKILLS - Barchinoy Hayitmurod qizi Rahmonqulova; Dilfuza Khudaykul kizi Iskandarova (PEDAGOGS, 2025)
Abstract: This article examines the importance of reading articles in language learning, focusing on its benefits to comprehension, vocabulary, critical thinking, and overall literacy development. In addition, reading articles regularly helps students enhance their reading fluency, which is understanding and analyzing information fully. By reading articles, learners find out various writing styles, structures, and topics which assists them to develop vocabulary, critical engagement, and strengthen the ability to understand information fully. In this paper, researchers explain the significance of reading articles and mention the findings of research about improving overall reading proficiency by reading articles.